Ambient Bistable Single Dipole Switching in a Molecular Monolayer. (4th June 2020) - Cui, Kang; Mali, Kunal S.; Wu, Dongqing; Feng, Xinliang; Müllen, Klaus; Walter, Michael; De Feyter, Steven; Mertens, Stijn F. L.
Abstract: Reported here is a molecular dipole that self‐assembles into highly ordered patterns at the liquid‐solid interface, and it can be switched at room temperature between a bright and a dark state at the single‐molecule level. Using a scanning tunneling microscope (STM) under suitable bias conditions, binary information can be written at a density of up to 41 Tb cm −2 (256 Tb/in 2 ). The written information is stable during reading at room temperature, but it can also be erased at will, instantly, by proper choice of tunneling conditions. DFT calculations indicate that the contrast and switching mechanism originate from the stacking sequence of the molecular dipole, which is reoriented by the electric field between the tip and substrate. Abstract : Molecular flip‐flop : By pulsing the tip voltage in a scanning tunneling microscope, individual molecules in a monolayer of a polyaromatic salt can be switched reversibly from a bright (0) to a dark (1) state, at room temperature and outside of a vacuum. The information density of this single‐molecule binary memory can reach up to 41 terabits per cm 2 .